2008
DOI: 10.1007/s11886-008-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the evaluation and management of syncope

Abstract: Syncope is a very common presentation with a wide differential diagnosis and equally wide prognostic implications. Recent work has highlighted the importance of an accurate history and physical examination as the basis of diagnosis, prognosis, and treatment. Several centers have evaluated the role of structured histories and comprehensive syncope evaluation guidelines and units in managing syncope. Although these do provide comprehensive care, whether they improve overall outcome and reduce costs is far from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…13 This is beyond the scope of the present review, which focuses exclusively on orthostatic intolerance. POTS is identified with chronic orthostatic intolerance 14-16 and is defined operationally by symptoms of OI in association with excessive tachycardia.…”
Section: Acute and Chronic Orthostatic Intolerancementioning
confidence: 93%
“…13 This is beyond the scope of the present review, which focuses exclusively on orthostatic intolerance. POTS is identified with chronic orthostatic intolerance 14-16 and is defined operationally by symptoms of OI in association with excessive tachycardia.…”
Section: Acute and Chronic Orthostatic Intolerancementioning
confidence: 93%
“…This data correlates with prior observational and small prospective randomized trials that have demonstrated pacemaker therapy efficacy in reducing recurrent syncope in the elderly. [18][19][20][21] Historically, however, unblinded trials in the therapy of syncope have provided divergent results, 22 reinforcing the need for large doubleblinded randomized approaches in this field. These results should also, however, be seen in the context of the Safepace 2 trial, 23 which, although double-blinded (yet underpowered), did only show a trend toward benefit with pacing versus implantable loop recording.…”
Section: Baselinementioning
confidence: 99%